Design, Fabrication, and Measurements of Extended L-Shaped Multiband Antenna for Wireless Applications - Ashfaq Ahmad; Farzana Arshad; Syeda I. Naqvi; Yasar Amin; Hannu Tenhunen, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This article expounds a multi-band compact shaped antenna, which is based on CPW ground plane. FR-4 with a thickness of 1.6 mm is used as a substrate for the proposed antenna. The proposed antenna is capable of operating at 1.56 GHz for (Global Positioning System), 2.45 GHz (Wireless Local Area Network) and 4.49 GHz (Aeronautical Mobile Telemetry (AMT) fixed services). The efficiency at 1.56, 2.45, and 4.49 GHz is 79.7, 76.9 and 76.7%, respectively. The VSWR of the presented antenna is less than 1.5 at all the desired resonance modes, which confirms its good impedance matching. The performance of the proposed antenna is evaluated in terms of VSWR, return loss, radiation pattern and efficiency. CST®MWS® software is used for simulations. In order to validate the simulation results, a prototype of the designed antenna is fabricated and a good agreement is found between the simulated and measured results.